RESPONSIVITAS WALIKOTA TERHADAP PERMASALAHAN YANG TERJADI DI KOTA PEKANBARU TAHUN 2015-2017 - Indrawansyah, Rian; ", Adlin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
This research is intended to know the evaluation of society to responsiveness of Mayor of Pekanbaru in overcoming the problem of relocation of street hawker in lotus street and waste management. This study focused on the response of Mayor to the public on the complaints of the services provided. Based on the background of the problem, this study aims to know and analyze the responsiveness of the mayor to the problems that occurred in the city of Pekanbaru 2015-2017. The research method used in this research is qualitative descriptive, with data collection techniques used is through observation, interviews, and documentation. The results of the field study showed that the assessment of street vendors in the lotus street and the people of Pekanbaru city to the responsiveness of the Mayor still not fully in accordance with the wishes society, This can be seen the results of research, observation and interviews that have been done by the author of six indicators of responsiveness by Zetihaml. The mayor has not met the indicators properly. From the results analyzed the authors pointed out that the lack of maximum service given by Mayor is due to lack of seriousness, speed, timeliness, and accuracy He in providing services to street vendors and people of Pekanbaru city. while for indicators of attitude and communication, as well as access provided by Mayor has been considered good because of his hospitality and the provision of access for people who want to complain to him. So in this study the authors concluded that the level of responsiveness Walikota Not fully responsive in responding to any complaints from the community for services that have been given.Keywords: Responsiveness, Public Service, Mayor